Britain's Sea Mammals : Whales, Dolphins, Porpoises, and Seals and Where to Find Them - Dunn, Jon (Conservationist); Harrop, Hugh; Still, Robert (Book collections on Project MUSE., 2014)
Britain's Sea Mammals is the essential field guide to all the sea mammals--whales, dolphins, porpoises, and seals--found in coastal Britain. The book features more than 100 stunning photographs and close to 40 detailed and beautiful illustrations of 34 species of sea mammals, paying special attention to the 14 species most readily seen and most likely to be encountered. Factoring in behavior and locations, introductory chapters look at sea mammal biology and ecology, and how, when, and where these creatures can be spotted. Species accounts highlight key identification characteristic.